KARAKTERISTIK BRIKET LIMBAH TONGKOL JAGUNG DENGAN PEREKAT TEPUNG BIJI NANGKA SEBAGAI BAHAN BAKAR ALTERNATIF - Ibrahim Hasan; Abdul Ghofur (Scientific Journal of Mechanical Engineering Kinematika, 2019)
Briquette is one of the alternative energy sources as a satisfactory substitute for fossil fuels in which the availability decreases every single day. The main materials of briquettes can be biomass. Biomass is an organic material produced by photosynthetic process, the materials may be product, remnant or waste. One of the potentially great biomass to be used as the main ingredient of briquettes is corncob. This study aims to (1) know the characteristics of corncob briquettes with adhesive jackfruit seed flour including moisture content, ash content, volatile matter and calorific value, (2) know the characteristics of the best corncob briquettes based on SNI standard. Corn cobs were converted first to charcoal with carbonization process, and then the charcoal was mixed with adhesive derived from jackfruit seed flour. In this study, variations of corncob to jackfruit seeds ratios were 90%: 10%, 85%: 15% and 80%: 20%, respectively. Then a mixture of charcoal and flour was molded with a molding pressure variation of 100 kg/cm2 and 120 kg/cm2. The parameters of briquette characteristics based on SNI 01-6235-2000 are moisture content, ash content, volatile matter and calorific value. The results show that the best characteristic briquettes is briquettes with sample code of B1 with charcoal to jackfruit flour ratio of 90% to 10% and printing pressure of 120 kg/cm2. The briquettes have water content characteristics of 7,0073%, ash content of 6,8876%, volatile matter of 17,8983% and calorific value of 6241,8137 cal/gram. But overall, the briquettes have not met the SNI 01-6235-2000 standards because the level of volatile matter in the briquettes exceed the maximum limit that has been determined i.e. 15%.